Mosaics - Rabin, Michael 1936-; Pommers, Leon (Capitol P8506, 1959)
Contains works, original and arranged by Chopin, Wieniawski, Mompon, Scriabin, Debussy, Sarasate, Elgar, Engel, Ravel, Prokofiev, & Suk.